On the preservation of the image of the architectural and urban planning complex of Adam Mickiewicz Square in Lviv - Bevz, Mykola (Teka Komisji Architektury, Urbanistyki i Studiów Krajobrazowych, 2023)
Abstract: In 2022−2023, a new hotel building appeared at Mickiewicz Square 9 in Lviv. It was built on the site of an architectural monument dating back to 1839. – the Gudec House. The project of the Gudec House was designed by Viennese architect Wilhelm Schmidt. The monument was dismantled despite the protests of the Lviv community and despite the decision of the Scientific and Methodological Council of the Ministry of Construction of Ukraine on the need for its restoration. In connection with the construction of the hotel, the city authorities announced plans to build an underground parking lot for 40 cars. This initiative sparked a great deal of discussion among monument conservationists and construction professionals. The site for the construction of the parking lot has a very complex hydrogeological structure, which greatly complicates the construction and can also negatively affect the entire historical environment of the square and the surrounding buildings. Another feature of the square is the presence of a number of archaeological sites. These are, first of all, the remains of two lines of fortifications – relics of the High Defense Wall of the 13th – 16th centuries. (in the area of the square are the remains of the Butchers’ tower and the wall curtain from it to the Coopers’ tower) and the remains of the so-called “third” defensive belt of the city center (a defensive line built in 1522−1542 in the form of large artillery corner towers and bastions; the corner towers were connected to each other by a rampart and a wall). These two defense lines had their own moats filled with water. In the 17th-18th centuries, when the fortification function faded away, buildings for various purposes were added to the defensive walls. Their remains may also be present in the underground space of the square. In the center of the square there is a monument to Adam Mickiewicz from 1904 – an object of unique artistic and architectural work. The purpose of this publication is to show what archaeological heritage sites are under the square and to point out the value of these relics for the history of Lviv. The discovery and archaeological disclosure of these monuments will make it impossible to build an underground parking lot here.